Unemployment Benefits in Argentina. Reflections Upon an Absence (1890-1989) - Grondona, Ana Lucia (Sociedad y Economía, 2014)
This article —based on the study of different documents of the archives— proposes aresearch agenda on the history of unemployment insurance in Argentina. We will discussdifferent periods that should help grasp the different reasons for which this formof regulation was blocked at different stages of the development of labor markets inArgentina between 1890 and 1989. We analyze five conjunctures relevant for our problem:a) 1913-1915; b) 1930-1939; c) 1940-1949; d) 1962-1970; e) 1975-1989. Although the reasons forthis absence varied, we point out some relevant issues throughout the different periods:the power balance between labor unions and employers, the impact experts have overthe State and the general labor market regulations (in relationship with the internationaldivision of labor).